Tectonic implications of U-Pb ages of detrital zircon grains in metasedimentary rocks of the northwestern sector of the Passos Nappe, southern Brasília Belt, Brazil - Silva, Alex J.Choupina A. [UNESP]; Simões, Luiz Sérgio A. [UNESP]; DuFrane, Scott Andrew (Elsevier, 2019)
The Estreito Anticline is the main structure in the northwestern sector of Passos Nappe, formed in the Late Neoproterozoic during West Gondwana amalgamation. It is characterized by folding of the thrust surface that separates the Passos Nappe from the Canastra Group. The hanging wall of the thrust includes lower units of the Passos Nappe (A, B and C units) and in the core of the fold (footwall) occur metasedimentary rocks of the Canastra Group and Metasiltite Unit. U-Pb dating of detrital zircon grains by LA-ICPMS from metasedimentary units of the Canastra Group shows contribution from a Neoarchean source (ca. 2.54–2.76 Ga) with minor contribution from Rhyacian source (∼ 2.10–2.30 Ga) with the youngest grain at 1.57 Ga. Results from the Passos Nappe samples show an important Rhyacian source (2.1 Ga), and a minor cluster with ages ranging from ca. 1.60 to 1.76 Ga (Statherian). Mesoarchean- Statherian terranes of the southwest margin of the São Francisco Craton represent the main sources of detrital sediments of the Passos Nappe and Canastra Group of a passive margin developed along the western margin of the continent. The U-Pb ages obtained for metasiltite show a broad distribution, with peaks between ∼0.54-0.70 Ga, and minor age groups ranging within 0.82–1.08 Ga, 1.60–1.97 Ga, 2.02–2.22 Ga and ∼2.60–2.85 Ga. The younger ages are compatible with the Bambuí Group exposed in the São Francisco Craton interior. An Ediacaran age for metasiltite in the fold interior suggests termination of deformation within the Passos Nappe at least the Early Cambrian.
Keywords: Bambuí group; Canastra group; Passos nappe; Southern Brasília belt; U-Pb zircon geochronology